BETA-BLOCKERS AND RENOPROTECTION: THE POTENTIAL OF CARVEDILOL - I. T. Murkamilov; I. S. Sabirov; V. V. Fomin; F. A. Yusupov (Столичная издательская компания, 2017)
The review presented the importance of carvedilol using in terms of renoprotection in renal dysfunction at the pre-dialysis stage of the disease in order to reduce the risk of progression of chronic kidney diseases (CKD) and the development of cardiovascular complications. Immune and non-immune mechanisms (proteinuria, dyslipidemia, anemia, arterial hypertension) of renal dysfunction progression in patients with CKD of inflammatory and non-inflammatory origin are described. Moreover, with the slowing down of the glomerular filtration rate in CKD, the role of non-immunefactors in the development of cardiovascular complications becomes very important. In contrast to non-selective and some β1-selective beta-blockers, the use of beta-adenoblocker with vasodilating activity, in particular carvedilol, makes it possible to prevent the onset of the terminal stage ofCKD. Carvedilol, being a lipophilic beta-adrenoblocker of the third generation with alpha-blocking properties, influences the possible mechanismsof renoprotection: antihypertensive (including in combined antihypertensive therapy), anti-inflammatory, antiproliferative, anti-apoptotic, antioxidant, antiplatelet and others. Carvedilol due to the vasodilating effect softens the stress of the parietal shear, exerting a retarding action on theprogression of CKD. Carvedilol with a pronounced vasodilating effect and a long half-life significantly reduces central arterial pressure that is also animportant renoprotective mechanism in the treatment of patients with renal dysfunction. Carvedilol has an important renoprotective mechanism in CKD - inhibition of the secretion of the potent vasoconstrictor endothelin. In the metabolic syndrome, in which there is a significant risk of developing renal dysfunction, carvedilol levels the imbalance of adipokine secretion, insulin resistance, sodium and water retention, and the activation of renin-angiotensin-aldosterone and sympathoadrenal systems. Carvedilol at the early stages of CKD development shows predominantly antihypertensive action due to inhibition of the renin-angiotensin-aldosterone system activity directly in the kidneys. At the late stage of the disease, the drug is able to retain residual kidney function. That is, carvedilol can be used at all stages of CKD development, regardless of the etiology of kidney damage.